Development of modular smart farm system - Nor Azlin, Ahmad Ammar; Mansor, Hasmah; Hashim, Ahmad Zawawi; Gunawan, Teddy Surya (2017)
Humans tend to rely on technology in almost everything they do in everyday life. To meet the demand of consumers, the agriculture industry has been improving their farming methods and techniques for maximum efficiency. This paper is focused on electronics, embedded systems and wireless technology to be integrated with farm monitoring, particularly in poultries. The system consists of two; master and slave. An array of sensors is used to measure the ambient temperature, ammonia at ppm level and humidity of the hall for each slave. The readings are then transmitted wirelessly over radio frequency by serial communication using HC-12 RF module to master for further data processing. The design process of both master and slave involved the interfacing of ATMEL ATMega328 with several analog sensors, passive and active components, LCD, buzzer, relay output, monetary push button and light indicator. The fan output parameter is controlled based on the set point defined from sensor readings. Furthermore, PID controller was integrated to optimize the output control method, hence optimizing hall condition which results to better output for the farm. The system has been successfully implemented and tested at Myra Farm & Services, located at Kalumpang, Tanjung Malim, Perak.